Designing and pilot testing of a leadership intervention to improve quality and safety in nursing homes and home care (the SAFE-LEAD intervention). Issue 6 (17th June 2019) - Johannessen, Terese; Ree, Eline; Strømme, Torunn; Aase, Ingunn; Bal, Roland; Wiig, Siri
Abstract : Objective: To describe the design of a leadership intervention for nursing home and home care, including a leadership guide for managers to use in their quality and safety improvement work. The paper reports results from the pilot test of the intervention and describes the final intervention programme. Design: Qualitative design, using the participation of stakeholders. Methods: The leadership guide and intervention were designed in collaboration with researchers, coresearchers and managers in nursing homes and home care organisations, through workshops and focus group interviews. The pilot test consisted of three workshops with managers working on the leadership guide, facilitated and observed by researchers, and evaluated by means of observation and focus group interviews with the participants. The analysis combined the integration of data from interviews and observations with directed content analysis. Setting: Norwegian nursing homes and home care services. Participants: Managers at different levels in three nursing homes and two home care services, coresearchers, and patient and next-of-kin representatives. Results: The managers and coresearchers suggested some revisions to the leadership guide, such as making it shorter, and tailoring the terminology to their setting. Based on their suggestions, we modified the intervention and developed learning resources, such as videos demonstrating the practical use of the guide. Evaluation of the pilot test study showed that all managers supported the use of the guide. They adapted the guide to their organisational needs, but found it difficult to involve patients in the intervention. Conclusions: A participatory approach with stakeholders is useful in designing a leadership intervention to improve quality and safety in nursing homes and home care, although patient participation in its implementation remains difficult. The participatory approach made it easier for managers to adapt the intervention to their context and to everyday quality and safety work practice.